2012
DOI: 10.1111/j.1365-2133.2012.10943.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of chronological ageing and photoageing in forearm skin using reflectance confocal microscopy

Abstract: Summary Background  Skin ageing is a complex process due to intrinsic chronological factors (chronoageing) and extrinsic environmental factors. The primary extrinsic factor is cumulative ultraviolet (UV) exposure, and is therefore termed photoageing. The current standards for measuring cumulative sun damage are biopsy histology and skin microtopography. However, skin biopsies are too invasive for population studies and skin replicas render only superficial skin architecture data. Reflectance confocal microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
129
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(152 citation statements)
references
References 31 publications
20
129
0
2
Order By: Relevance
“…This is often observed in individuals with sundamaged skin and thus it differs to skin on other body areas, eg, forearm where skin architecture at dermoepidermal junction is usually characterized by round architecture of dermal papillae. 21 …”
Section: Methodsmentioning
confidence: 99%
“…This is often observed in individuals with sundamaged skin and thus it differs to skin on other body areas, eg, forearm where skin architecture at dermoepidermal junction is usually characterized by round architecture of dermal papillae. 21 …”
Section: Methodsmentioning
confidence: 99%
“…RCM provides higher resolution imaging allowing for assessment of structural morphology changes and also allows for serial imaging over time [39]. More than 15 statistically significant RCM features are associated with forearm photoaging, including changes in architecture, cell morphology, and collagen at the level of the epidermis, dermo-epidermal junction, and papillary dermis [48]. In this study, the authors were able to mathematically correlate RCM-identified photoaging with conventional scoring techniques including the SCINEXA scale and photograph scale.…”
Section: Other Methods Of Photoaging Assessmentmentioning
confidence: 95%
“…With aging, skin surface change its appearance gradually [1] due to intrinsic chronological factors and extrinsic environmental factors [2]. The most used techniques for measuring skin surface topography was the skin surface replicas analysis [3].…”
Section: Introductionmentioning
confidence: 99%